Study the Pharmacological Effect of Letrozole and Gonadotropine on the Level of Serum Glycoprotein’s (HRG, Inhibin B, and AMH) in Infertile Women and their Effect on Stimulating Ovulation - Narjis Hadi Al-Saadi (Journal of Global Pharma Technology, 2018)
Objective: To study the effect of medication (letrozole, and gonadotropine) on ovulation induction and its relation with glycoproteins. Methods: Thirty-three infertile women were enrolled from outpatient women’s clinic and twenty-two healthy fertile women were enrolled as a control group. Their ages ranges from (15 to 44) years old. Histidine Rich Glycoprotein (HRG), Inhibin B and Anti Müllerian hormone (AMH) concentrations were measured in sera using (ELISA) technique. Results: Follow-up examinations four months after receiving treatments revealed a significant raise in serum HRG concentration (p=0.01) and a considerable decrease in serum AMH concentration (p=0.04) among infertile women. Pelvic ultrasonography, showed a significant (p = 0.000) increase in the size and the number of oocytes in both left and right ovaries infertile women.  Conclusion: Letrozole and gonadotropin treatments are effective in changing the levels of HRG and AMH in infertile women. Keywords: Women infertility, HRG, Inhibin B, AMH, letrozole, gonadotropin.